Lycopene Protects Cortical Neurons via Oxidative Stress-mediated ΔN-Bcl-xL Formation (FS05-08-19) - Stumpf, Allison (Curr Dev Nutr, 2019)
OBJECTIVES: B-cell lymphoma-extra large (Bcl-xL) is a protein found in the mitochondrial membrane with anti-apoptotic properties. Bcl-xL has demonstrated neuroprotective effects by enhancing mitochondrial function. However, during oxidative stress, Bcl-xL undergoes cleavage to form pro-cell death ∆N-Bcl-xL. Accumulation of ∆N-Bcl-xL causes abnormal mitochondrial channel activity associated with neuronal death. Therefore, strategies that prevent formation of ∆N-Bcl-xL protect the brain. In this study, we hypothesize that cleavage of Bcl-xL can be controlled by nutritional intervention. We test if treatment with lycopene, a potent antioxidant with neuroprotective effects, can protect primary neurons via improving intracellular redox status by reducing production of ∆N-Bcl-xL. METHODS: Primary cortical neurons were treated with lycopene, hydrogen peroxide (a ROS donor), or both. Levels of superoxide, cell viability and cytotoxicity, and protein levels of Bcl-xL and ∆N-Bcl-xL were quantified. RESULTS: Hydrogen peroxide increased cytotoxicity while treatment with lycopene protected oxidative stress-induced cortical death. Lycopene prevented N-terminal cleavage of Bcl-xL and thus inhibited formation of ∆N-Bcl-xL. CONCLUSIONS: These data show that the formation of ∆N-Bcl-xL is induced in part by reactive oxygen species and high levels of oxidative stress. The antioxidant properties of lycopene help reduce oxidative stress and prevent cleavage of Bcl-xL to ∆N-Bcl-xL, thus maintaining an anti-apoptotic environment. FUNDING SOURCES: RG14811.